ELECTORAL JUSTICE AND AUTOMATED DISINFORMATION: REFLECTIONS ON DEEPFAKES AND DEMOCRATIC SECURITY - Andrade Silva, Emilly Beatriz; Coelho Nunes Campos, Débora; Aguiar de Alencar, Kalyne Laura; Cunha Santos, Kassandra Kelly; Ribeiro Ferreira Façanha, Josanne Cristina (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This article examines the increasing use of automated disinformation tools, with particular focus on deepfakes technologies, within the Brazilian Electoral Justice framework. The rapid development of generative artificial intelligence has intensified audiovisual manipulation and the spread of fake news, significantly affecting the integrity of democratic processes, especially during electoral periods. The study employs a descriptive and exploratory methodology, based on legal doctrine, analysis of the Superior Electoral Court (TSE) regulations, and technical studies in digital governance. Findings suggest that although initiatives such as the Program to Combat Disinformation and partnerships with digital platforms exist, substantial challenges persist regarding the detection of synthetic content, accountability of automated agents, and protection of free expression. It is concluded that the Electoral Justice must strengthen regulatory mechanisms, transparency strategies, and media literacy initiatives, implementing preventive and investigative measures capable of mitigating deepfakes’ impacts and ensuring electoral security in an increasingly complex digital environment.